(untitled) (Economic and Political Thought, 2015)
The article is a theoretical and research study. The theoretical part presents the characteristics of the drug reimbursement system in Poland. The empirical part presents the results of empirical research designed to identify main pathologies and weaknesses in the current practice of the system, with particular regard to the pharmacy Rx medications retail and wholesale market. The paper thoroughly presents three of the six categories of weaknesses and pathologies diagnosed, based on the results of the empirical research, i.e. rewarding patients with the use of rebates and discounts mechanisms (i.e. drugs for a penny) for providing pharmacies with prescriptions; changes in the price of the drug after its introduction/removal from the list of reimbursed drugs, which are disadvantageous to the public payer (and/or a patient); limiting the availability of medicines in the domestic market resulting from legal and illegal parallel export as a consequence of low official domestic prices, and wholesale and pharmacy margins. The results of the study have been used to formulate general conclusions regarding valid reasons to proceed with the improvements to the reimbursement system.